Sensory stimulation program improves developments of preterm infants in Southwest China: A randomized controlled trial - Zheng, Wenjing; Chotipanvithayakul, Rassamee; Ingviya, Thammasin; Xia, Xiaoling; Xie, Lu; Gao, Jin (Frontiers in Psychology, 2022)
Preterm infants are prone to growth and developmental delay, especially social-emotional development. Sensory stimulation may benefit developmental outcomes for these vulnerable infants. This study aims to determine whether 5-integrated sensory stimulation (5-ISS) improves preterm infant social-emotional development. A randomized, parallel trial was conducted from November 2018 to January 2020 at three tertiary hospitals in Kunming, China. Preterm infants were eligible if gestational ages were from 28 to 36 weeks based on ultrasound results when discharged from neonatal wards. Two hundred preterm infants (male n = 110, female n = 90) were randomly allocated to the 5-ISS intervention group (n = 98) and the standard care group (n = 102). Social-emotional development was assessed with the Ages and Stages Questionnaires: Social-Emotional (ASQ:SE). Temperament was assessed with the Infant Behavior Questionnaire-Revised. Anthropometry, which included weight, length, and head circumference, was measured at corrected ages of 1, 3, and 6 months. Demographic and clinical characteristics were similar between the intervention and the standard care groups. At 1- and 3-month corrected age, no significant differences between the two groups were observed in terms of infant development and temperament. At 6 months, significant disparities were found in the social-emotional development scale (mean difference −0.29, 95% CI: −0.58, < -0.001, p = 0.01), infant length (mean difference 0.70, 95% CI: < 0.001, 1.4, p = 0.03), distress to limitation (p = 0.04), and sadness (p = 0.03). A mixed model revealed that the 5-ISS intervention positively affected social-emotional development, length, distress to limitation, and sadness for preterm infants. Integrated sensory stimulation has benefits on social-emotional development, temperament, and length for preterm infants. This program provides a feasible method to promote social-emotional development for preterm infants.